Cover Feature: Mechanoenzymatic Breakdown of Chitinous Material to N‐Acetylglucosamine: The Benefits of a Solventless Environment (ChemSusChem 15/2019). Issue 15 (1st August 2019) - Therien, J. P. Daniel; Hammerer, Fabien; Friščić, Tomislav; Auclair, Karine
Abstract : The Cover Feature shows the mechanoenzymatic saccharification of chitin by chitinases in the absence of bulk water. Based on brief repeating cycles of ball milling followed by static incubation, this reactive‐aging (RAging) method is closer to the natural environment of chitinase enzymes and enables the clean and efficient production of  N ‐acetylglucosamine directly from shrimp or crab shell biomass. More information can be found in the Full Paper by J. P. D. Therien et al. on page 3481 in Issue 19, 2015 (DOI: 10.1002/cssc.201901310 ).